(untitled) (Международный научный журнал «Инженер», 2026)
This study introduces a methodology for evaluating the embodied carbon of building materials and structural elements. The approach includes relevant formulas and step-by-step procedures to systematically assess carbon emissions associated with material production and construction processes. While actual numerical results are not presented in this work, the methodology provides a framework for applying these calculations in practice. Operational carbon is not considered in this study but is identified as a topic for future research. Overall, the proposed methodology offers a structured approach to analyzing embodied carbon, supporting further studies and adaptations in construction projects aimed at sustainable development.